Going to the wars : the experience of the British civil wars, 1638-1651 - Carlton, Charles, 1941- (Routledge, 1992)
During the 1640s, tens of thousands of young British men set off for the Civil Wars full of that innocent enthusiasm with which so many before and since have welcomed the prospect of battle. Few had much idea of the reality of war. Brought up in a relatively peaceful society, they were totally unprepared for the military discipline, the physical exhaustion, the divided loyalties, the emotional strain, the loneliness, and, above all, the violence of combat. Going to the Wars studies the British Civil Wars as a military experience. It is not a traditional campaign history, a political history of the war, or an analysis of weapons, organization, supply or tactics. Rather it explains how men prepared for combat, how they campaigned, fought battles and endured sieges. Others also endured the horrors of war, and the book pays special attention to those often excluded from a military panorama: women, children and prisoners of war.